Mengelola Kapasitas Produksi untuk Memperoleh Keuntungan Maksimum dengan Linear Programming Metode Simpleks (Studi Kasus Cireng Isi Ayam dan Isi Keju) - Sandrina, Alya; Aulya, Shindy Putri; Azzahwa, Vasya; Firdaus, Farid; Fariz, Roenal; Palahudin, Palahudin (Innovative: Journal Of Social Science Research, 2025)
This research aims to optimize the production capacity of chicken shredded-filled cireng and cheese-filled cireng using the linear programming method with the simplex approach. In the snack food industry in Indonesia, cireng has become one of the popular products, but business operators often face challenges in managing resources efficiently. Through the analysis conducted, a mathematical model was obtained that includes relevant objective functions and constraints, enabling business operators to maximize profits. The research results show that the UMKM cireng factory can achieve a maximum production of up to 300 times per day with a profit of Rp 3,000,000. This research is expected to provide strategic guidance for business actors in production management and decision-making, as well as contribute to the development of literature in the fields of managerial economics and sustainability of UMKM in Indonesia.